Synthesis and characterization of simple cost-effective trans-A(2)BC porphyrins with various donor groups for dye-sensitized solar cells - Kumar, Ravi; Sankar, Muniappan; Sudhakar, Vediappan; Krishnamoorthy, Kothandam (New Journal of Chemistry, 2016)
We have designed and synthesized a series of simple cost-effective 'push-pull' Zn(II) porphyrin dyes containing various electron donors such as 2-thienyl, pyrenyl, phenyl, 4'-bromophenyl, 4'-tbutylphenyl and 4'-carboxyphenyl acceptor moieties in three steps. Their optical absorption spectra, electrochemical redox and photovoltaic properties have been investigated in detail. The overall power conversion efficiencies (Z) of DSSCs based on these dyes are in the range of 2.1 to 4.2% and highly depend on their donor moiety. The incorporation of trans-10,20-dimesityl groups is highly beneficial for preventing the p-p aggregation among the porphyrin moieties, thus favorably suppressing the charge recombination and intermolecular interaction. Among all, pyrenyl appended Zn(II) porphyrin has exhibited a higher power conversion efficiency of 4.2% under 1 sun illumination due to the extended p-conjugation and electron donating ability of the pyrenyl moiety.

Trans-A(2)B(2) Zn(II) porphyrin dyes with various donor groups and their Co-sensitization for highly efficient dye-sensitized solar cells - Prakash, Kamal; Sudhakar, Vediappan; Sankar, Muniappan; Krishnamoorthy, Kothandam (Dyes and Pigments, 2019)
{We have designed and synthesized four donor-acceptor based trans-A(2)B(2) Zn(II) porphyrin dyes with various donor moieties and phenylcarboxy as acceptor group in three steps. Two strong electron-donating groups (carbazole, phenothiazine, pyrene and bisthiophene) were attached to porphyrin core to enhance the light absorption of dye molecules and phenylcarboxy acted as acceptor group on TiO2 surface. The alkyl chains present in KP-Zn-CBZ and KP-Zn-PTZ dyes are helpful to suppress the aggregation of dyes at the semiconductor surface. The synthetic route of these dyes was facile, high yield and three steps procedure which involved MacDonald condensation followed by hydrolysis and Zn insertion. The absorption and emission bands of all four dyes were broadened and red shifted due to the charge transfer from donor groups to porphyrin moiety. A wide range of power conversion efficiency was shown by dyes and the order of eta was as followed KP-Zn-PTZ (5.48%) > KP-Zn-PYR (3.38%) > KP-Zn-CBZ (2.64%) > KP-Zn-BTP (1.71%). Co-sensitization of porphyrin dyes with N719 dye promoted the complementary absorption in the visible region and put a restriction on dye aggregation also which improved the cell performance. Co-sensitized KP-Zn-PTZ with N719 dye showed the highest PCE efficiency up to 8.80% with a J(SC) = 17.4 mA cm(-2)